Pengaruh Perilaku Variety Seeking terhadap Brand Switching Produk Kosmetika Remaja Putri di Negeri Hatalai - Pattiruhu, Maudy Hendriny; Pelamonia, Merryl; Tupamahu, Fenri Abraham (Jurnal Pendidikan Ekonomi, 2023)
The competition among cosmetic products for teenage girls is intensifying, encouraging consumer behavior to seek variety and frequently switch brands. This study aims to analyze the influence of Variety Seeking behavior on Brand Switching of cosmetic products among teenage girls in Hatalai Village. The research employed a quantitative approach using questionnaires distributed to young female respondents. Data were tested for validity, reliability, and analyzed using simple regression analysis. The results indicate that Variety Seeking behavior—including the desire to try new products, the need for variety, and perceived differences among brands—significantly affects cosmetic brand switching. These findings show that higher intensity of Variety Seeking behavior increases the tendency of teenage girls to switch brands. The conclusion highlights the importance of understanding consumer behavior in designing marketing strategies for cosmetic products. The implication is that cosmetic businesses should continually innovate product variations, strengthen brand attachment, and enhance marketing communications to maintain teenage consumer loyalty amid dynamic competition